THE ROLE OF ENERGY TRANSITION AND INTENSITY ON CO2 IN OECD COUNTRIES - Esha Galang Gati Mahendra; Toto Gunarto; Neli Aida (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The purpose of this study was to analyze the influence of GDP per capita, renewable energy consumption, and energy intensity on CO2 emissions in 38 OECD member countries during the period 2010–2022.This study uses a quantitative approach and panel data regression The results of this study found that all independent variables have a significant influence on CO2 emissions. GDP per capita and energy intensity have a positive effect, with elasticities of 0.060% and 0.67%, respectively, indicating that economic growth and energy inefficiency increase emissions. In contrast, renewable energy consumption had a negative effect with an elasticity of -0.016%, confirming the important role of clean energy in reducing emissions. These findings are in line with the Environmental Kuznets Curve (EKC) hypothesis and emphasize the urgency of the energy transition and improving energy efficiency in developed countries.